PENGARUH BERKUMUR DENGAN EKSTRAK STROBERI (Fragaria x ananassa Duchesne) TERHADAP PERTUMBUHAN PLAK PADA ANAK UMU R 11-12 TAHUN - , FEBRY PRADYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Strawberry extract has widely known to have an advantage for protect oral health because of its contain flavonoid. Flavonoid as compound which have antibacterial activity to destruct bacteria wall that can inhibit the plaque formation. Plaque control can also be done as an effort to inhibit the plaque formation, one of which is by rinse out. This research was done to 30 subjects, 11-12 years old from Madrasah Ibtidaiyah Sunan Pandan Aran, Sleman. This research is a quasi experimental study with a crossover design approach. Every subject received treatments, for first group of 15 subjects rinsing out with strawberry extract and second group of 15 subjects rinsing out with water as control. The subject rinse 3 days every morning after a meal and night before sleep with a volume 10cc and rinse during 30 seconds. Do washout period of 1 week to normalize the condition of the oral cavity, and then the subject groups exchanged. First group rinsing out with water and second group rinsing out with strawberry extract, done for 3 days as before. Independent t-test used to determine the effect of strawberry extract rinse on plaque score of 11-12 years old children. Statistical analysis showed that there was a significant difference of plaque score between rinsing out with water and rinsing out with strawberry extract. Based on this result, it can concluded that rinsing out with strawberry extract was affected to inhibit plaque formation of 11-12 years old children.